Dual-Tasking in Multiple Sclerosis – Implications for a Cognitive Screening Instrument - Beste, Christian; Mückschel, Moritz; Paucke, Madlen; Ziemssen, Tjalf (Frontiers in Human Neuroscience, 2018)
The monitoring of cognitive functions is central to the assessment and consecutive management of Multiple Sclerosis (MS). Though, especially cognitive processes that are central to everyday behavior like dual-tasking are often neglected. We examined dual-task performance using a psychological-refractory period (PRP) task in N = 21 patients and healthy controls and conducted standard neuropsychological tests. In dual-tasking, MS patients committed more erroneous responses when dual-tasking was difficult. In easier conditions, performance of MS patients did not differ to controls. Interestingly, the response times were generally not affected by the difficulty of the dual task, showing that the deficits observed do not reflect simple motor deficits or deficits in information processing speed but point out deficits in executive control functions and response selection in particular. Effect sizes were considerably large with d~0.80 in mild affected patients and the achieved power was above 99%. There are cognitive control and dual tasking deficits in MS that are not attributable to simple motor speed deficits. Scaling of the difficulty of dual-tasking makes the test applied suitable for a wide variety of MS-patients and may complement neuropsychological assessments in clinical care and research setting.